1484. Microbial Etiology of Community-acquired Pneumonia in Immunocompromised Patients. (31st December 2020) - Deshpande, Abhishek; Yu, Pei-Chun; Rothberg, Michael
Abstract: Background: Community-acquired pneumonia (CAP) is a leading cause of infection related mortality. Few studies have specifically evaluated the microbial etiology of CAP in immunocompromised patients. Using a large national inpatient database, we compared the microbial etiology of CAP in immunocompromised patients compared to immunocompetent patients. Methods: We included adult patients admitted with pneumonia from 2010-2015 to 176 US hospitals participating in Premier. Patients were identified as having CAP if they had a chest X-ray and were on antimicrobials on the first day. Immunocompromised was defined by the receipt of immunosuppressive medications or ICD-9 codes for neutropenia/ hematological malignancy/ organ transplantation or comorbidities with AIDS. For microbial etiology, patients were included if they had a positive culture or test collected by hospital day 0 through 3. Patients with identical bacteria in blood and urine were excluded. Results: A total of 168, 159 patients had a diagnosis of CAP with a culture/test performed on first 3 days. A pathogen was detected in 18.8% of patients. Among pathogen positive patients, 4, 851 patients were identified as immunocompromised and 26, 752 as immunocompetent. Almost all patients (99%) had at least one culture, blood (96%) and respiratory (51%). Among patients who were immunocompromised, the most common bacterial pathogens (compared to immunocompetent patients) were, S. pneumoniae (17.7% vs 19.0%), MRSA (13.1% vs 14.4%), MSSA (12.0% vs 11.8%), P. aeruginosa (12.0% vs 9.9%), E. coli (7.4% vs 6.4%), K. pneumoniae (5.8% vs 4.9%), H. influenzae (5.5% vs 5.5%), M. pneumoniae (3.0% vs 3.0%) and L. pneumophila (0.93% vs 1.2%). Among viral pathogens, while the most common were influenza virus (12.9% vs 14.1%) followed by rhinovirus (1.5% vs 0.89%), immunocompromised patients has a higher prevalence of noninfluennza viruses (3.42% vs 2.43%). Conclusion: In a large US inpatient sample, the causative organisms in immunocompromised patients did not differ much from those in immunocompetent patients. CAP pathogens in immunocompromised patients were more likely to involve gram-negative bacilli such as P.aeruginosa and E.coli, than gram-positive cocci. These findings may have implications when deciding on empiric therapy in these patients. Disclosures: Abhishek Deshpande, MD, PhD, Ferring Pharmaceuticals (Advisor or Review Panel member)Merck (Consultant)